The perception of ESL teachers in selected Malaysia primary schools on school based assessment system / Kamisah Mat Said - Mat Said, Kamisah (2015)
This study was a survey on the perception of ESL teachers on the implementation of school based assessment (SBA) in Malaysia public schools. The focus of the study is to seek information based on three main aspects namely 1) the teachers’ level of readiness/ preparedness in implementing SBA, 2) the teachers’ perceived effectiveness of SBA, and 3) the current issues and concerns regarding the implementation of SBA in school level. The respondents of this study consisted of 83 ESL teachers from 32 schools in Kuala Krai, Kelantan. The teachers were asked to complete a questionnaire to provide information for this study. The result of this study has shown that teachers’ level of readiness/ preparedness and confidence level to conduct SBA in schools were not at a satisfactory level, and teachers did not feel that the school-based assessment has been effectively implemented in schools.Significantly, the respondents of this study preferred to terminate SBA if they were given a choice. The respondents had indicated that time constraint, class size, documentation and records, teaching materials and sources of reference, support and professional development were among the issues and concerns that need to be addressed by all educational stakeholders in Malaysia if SBA is deemed to be successful. This research can be taken as a reference by all educational stakeholders in rectifying the issues related to the implementation of school based assessment